2019
DOI: 10.1136/rmdopen-2019-000912
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness in patients with rheumatoid arthritis is associated with the patient global assessment but not with objective measurements of disease activity

Abstract: ObjectivePatients with rheumatoid arthritis (RA) suffer from more cardiovascular disease (CVD), and develop cardiovascular risk factors at an earlier age than the general population. Cardiorespiratory fitness (CRF) is an important predictor of cardiovascular health. There are few data regarding CRF of RA patients, measured as peak oxygen uptake (VO2peak) by the gold standard method; cardiopulmonary exercise testing. We compared CRF in RA patients to those from a healthy population, and investigated if risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 47 publications
(40 reference statements)
3
24
2
2
Order By: Relevance
“…Thus, more recent exercise regimens for RA patients could potentially have counteracted the decline in eCRF from HUNT2 to HUNT3. This does not seem to have had a strong effect because a study from our group showed that RA patients tested in 2017 still had reduced CRF compared to the healthy population [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, more recent exercise regimens for RA patients could potentially have counteracted the decline in eCRF from HUNT2 to HUNT3. This does not seem to have had a strong effect because a study from our group showed that RA patients tested in 2017 still had reduced CRF compared to the healthy population [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because HUNT is a large population-based study, RA disease-related variables that would not be relevant for controls such as disease activity, swollen and tender joint counts, or the patient’s global disease assessment were not collected. Previously, our group found that a number of variables describing physical function and disease activity were not associated with measured CRF at CPET in RA patients and did not improve the RA-specific eCRF equation [ 15 , 16 ]. Thus, the results of the present study are probably not biased because such variables were missing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 CRF is, therefore, an important modifiable risk factor because it may be improved by increasing relevant physical activity (PA). 20 Studies have shown that patients with RA have reduced CRF compared with the healthy population, [21][22][23] whereas PA interventions that improve CRF are associated with increased function and reduction of cardiovascular risk in RA. 24 25 The gold-standard method to measure VO 2max is by cardiopulmonary exercise testing (CPET) either on a treadmill or bicycle ergometer.…”
Section: Rmd Openmentioning
confidence: 99%